Clinical practice patterns of isthmic spondylolysis in young athletes: a survey of pediatric research in sports medicine members - Hollabaugh, W. L.; Davelaar, C. M. F.; McHorse, K. J.; Achar, S. A.; MacDonald, J. P.; Riederer, M. F. (Current Sports Medicine Reports, 2022)
Isthmic spondylolysis is a common cause of back pain in young athletes. The condition presents to numerous medical providers who employ a variety of different practices in diagnosis and management. The purpose of this study was twofold: to review the literature of diagnosis and management of the young athlete with isthmic spondylolysis and to survey Pediatric Research in Sports Medicine (PRiSM) members during the 2021 PRiSM Annual Meeting on practice patterns of diagnosis and management of the young athlete with isthmic spondylolysis. The response rate was 27%. Per respondents: 24% obtain oblique radiographs; 90% use magnetic resonance imaging as the advanced imaging modality; 60% treat with bracing; 57% recommend rest prior to physical therapy (PT); 53% prescribe return to sport activity restrictions. Although there are similarities in the diagnosis of isthmic spondylolysis in young athletes, this survey confirmed variability in management, especially bracing, timing of PT and return to sport activity restrictions.